Be the boss everyone wants to work for : a guide for new leaders - Gentry, William A. (Berrett-Koehler Publishers, Inc : Center for Creative Leadership, 2016)
Flip Your Script! You've been promoted to leadership?congratulations! But it's nothing like your old job, is it? William Gentry says it's time to flip your script. We all have mental scripts that tell us how the world works. Your old script was all about "me": standing out as an individual. But as a new leader, you need to flip your script from "me" to "we" and help the group you lead succeed. In this book, Gentry supports and coaches you to flip your script in six key areas. He offers actionable, practical, evidence-based advice and examples drawn from his research, his work with leaders, and his own failures and triumphs of becoming a new leader. Get started flipping your script and become the kind of boss everyone wants to work for